2018
DOI: 10.1186/s40069-018-0272-5
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of FRP-Strengthened RC Beams with Large Rectangular Web Openings in Flexure Zones: Experimental and Numerical Study

Abstract: This paper aims to investigate the behavior of fiber reinforced polymer (FRP) strengthened reinforced concrete (RC) beams containing large rectangular web openings in the flexure zone. Studied parameters were type of loading, opening size and strengthening scheme. Seven RC beams categorized into two different groups were tested. In the first group, two unstrengthened beams (one solid without opening and one with large rectangular web opening in the pure flexure zone) were tested under four-point bending. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 28 publications
(30 reference statements)
0
33
0
1
Order By: Relevance
“…A number of studies have been reported in the literature on the behavior and strength of reinforced concrete deep beams with openings (Ashour and Rishi, 2000; Jasim et al, 2018; Kong and Sharp, 1977; Mansur and Alwis, 1984; Shanmugam and Swaddiwudhipong, 1988). Some researchers studied the effect of strengthening, using carbon fiber–reinforced polymer (CFRP) around openings, on upgrading the strength of flexural concrete members (Abdalla et al, 2003; Almusallam et al, 2018; El-Maaddawy and Sherif, 2009; Hawileh et al, 2013; Mansur and Tan, 1999; Nie et al, 2018).…”
Section: Introduction and Research Significancementioning
confidence: 99%
“…A number of studies have been reported in the literature on the behavior and strength of reinforced concrete deep beams with openings (Ashour and Rishi, 2000; Jasim et al, 2018; Kong and Sharp, 1977; Mansur and Alwis, 1984; Shanmugam and Swaddiwudhipong, 1988). Some researchers studied the effect of strengthening, using carbon fiber–reinforced polymer (CFRP) around openings, on upgrading the strength of flexural concrete members (Abdalla et al, 2003; Almusallam et al, 2018; El-Maaddawy and Sherif, 2009; Hawileh et al, 2013; Mansur and Tan, 1999; Nie et al, 2018).…”
Section: Introduction and Research Significancementioning
confidence: 99%
“…Previous research studies have been conducted on the behavior and strengthening of simply supported reinforced concrete deep beams with and without openings [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 ]. The creation of rectangular and circular openings in shear spans of the reinforced concrete deep beams affect the load-carrying capacity, where the reduction of the failure load reached 66% [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Failure loads are largely affected by the strengthening scheme and are slightly affected by spacing. Tarek et al [6] investigated the response of FRP strengthened RC beams containing large rectangular web openings in the flexure zone. Parameters studied included type of loading, opening size, and strengthening scheme.…”
Section: Introductionmentioning
confidence: 99%